Health tourism on San Pedro del Pinatar saltworks and Sandy Areas Regional Park (Murcia, SE Spain) - Ballesteros Pelegrín, Gustavo (M+A. Revista Electrónica de Medioambiente, 2015)
Health tourism in the Regional Park of the Salinas de San Pedro del Pinatar, is located in the mud pond baths next to the town of Lo Pagan. The number of visitors has increased from less than 100,000 people in the late twentieth century, more than 223,000 people in 2010. Building a car park and a series of walkways that provide access to the beach improved these facilities remarkably. Both were made by the Regional Public Administration in 2003, and an environmental rehabilitation project on the road that runs between the Quintin mill and La Calcetera one, executed by the National Ministry of Environment in 2005. On a year basis, in August, when maximum number of visitors occurred, this area seems to have reached maximum carrying capacity, as the data shows from 1984, a steady number of visitors estimated at about 50,000 people.
Keywords: Health Tourism; Regional Park; Mud Pond; Visitors.